Structural and microstructural predictors of cognitive decline in deep brain stimulation of subthalamic nucleus in Parkinson's disease - Filip, Pavel; Mana, Josef; Lasica, Andrej; Keller, Jiří; Urgošík, Dušan; May, Jaromír; Mueller, Karsten; Jech, Robert; Bezdicek, Ondrej; Růžička, Filip (NeuroImage. Clinical, 2024)
BACKGROUND AND OBJECTIVES: The intricate relationship between deep brain stimulation (DBS) in Parkinson's disease (PD) and cognitive impairment has lately garnered substantial attention. The presented study evaluated pre-DBS structural and microstructural cerebral patterns as possible predictors of future cognitive decline in PD DBS patients. METHODS: Pre-DBS MRI data in 72 PD patients were combined with neuropsychological examinations and follow-up for an average of 2.3 years after DBS implantation procedure using a screening cognitive test validated for diagnosis of mild cognitive impairment in PD in a Czech population - Dementia Rating Scale 2. RESULTS: PD patients who would exhibit post-DBS cognitive decline were found to have, already at the pre-DBS stage, significantly lower cortical thickness and lower microstructural complexity than cognitively stable PD patients. Differences in the regions directly related to cognition as bilateral parietal, insular and cingulate cortices, but also occipital and sensorimotor cortex were detected. Furthermore, hippocampi, putamina, cerebellum and upper brainstem were implicated as well, all despite the absence of pre-DBS differences in cognitive performance and in the position of DBS leads or stimulation parameters between the two groups. CONCLUSIONS: Our findings indicate that the cognitive decline in the presented PD cohort was not attributable primarily to DBS of the subthalamic nucleus but was associated with a clinically silent structural and microstructural predisposition to future cognitive deterioration present already before the DBS system implantation.
Keywords: Magnetic Resonance Imaging; Subthalamic nucleus; magnetická rezonanční tomografie; Humans; neuropsychologické testy; lidé středního věku; Deep Brain Stimulation; Female; Aged; Deep brain stimulation; senioři; lidé; nucleus subthalamicus; Diffusion tensor imaging; Parkinson’s disease; Neuropsychological Tests; ženské pohlaví; Male; Middle Aged; hluboká mozková stimulace; Cognitive Dysfunction; Subthalamic Nucleus; Diffusion weighted imaging; mužské pohlaví; Parkinson Disease; kognitivní dysfunkce; Parkinsonova nemoc